An Experimental Approach to Characterizing the Channel Local Temperature Induced by Self-Heating Effect in FinFET - E Ray Hsieh (IEEE Journal of the Electron Devices Society, 2018)
In this paper, we have developed a methodology of a lateral profiling technique of the channel local temperature in 14 nm FinFET, incurred by the self-heating effect (SHE). As SHE happens, the thermal source generated near the drain will dissipate toward the source side. Since the interaction between RTN trap and channel carriers is very sensitive to the temperature, the channel local temperature can be extracted through this interaction process between random-telegraph-noise (RTN) trap and carriers, and the position of the channel local temperature can be obtained from the RTN trap position. The results show that the highest temperature happens at the drain edge during SHE and pFinFET exhibits a much higher temperature than that of nFinFET. Furthermore, the distribution of channel local temperature can be described by the Fourier's law of thermal conduction. Averaged channel temperature can be used to extract the thermal resistance, Rth, which increases rapidly as the channel length is scaled down to 20 nm, further degrading the SHE, in terms of a significant short channel effect. We also found that the incremental channel resistance is proportional to the incremental channel local temperature, whose slope indicates the degree of SHE, and the slope of pFinFET is larger than that of nFinFET. Finally, SHE will cause 10% and 14% degradation of IdVds for nand pFinFET respectively. This can be reasonably explained by the decay of saturation velocity in high temperature. The results obtained based on this methodology will help us on the understanding of the SHE impact on a nano-scaled FinFET device.